Uruguay : 2001 Article IV Consultation and First Review under the Stand-By Arrangement - Staff Report; Public Information Notice and News Brief on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2001)
After the recession, Uruguay continued to face difficult economic conditions under the Stand-By Arrangement. Executive Directors emphasized the need to promote sustainable growth with low inflation and high employment. They welcomed Uruguay's continued commitment to trade liberalization, and stressed the need for fiscal discipline, improved competitiveness, strong fiscal and monetary policies, structural reforms, and measures to strengthen the performance of public enterprises. They observed that the country's economic statistics are adequate for the assessment and monitoring of macroeconomic policies.